2020
DOI: 10.1002/adfm.202003935
|View full text |Cite
|
Sign up to set email alerts
|

Pt Dopant: Controlling the Ir Oxidation States toward Efficient and Durable Oxygen Evolution Reaction in Acidic Media

Abstract: Dissolution of Ir oxides in Ir‐based catalysts, which is closely linked to the catalyst activity and stability toward the oxygen evolution reaction (OER) in acidic media, is a critical unresolved problem in the commercialization of water electrolysis. Doping foreign elements into the Ir oxides can accomplish an optimal combination of Ir oxidation states that is conducive to the leaching‐resistance of active catalytic sites. Here, it is reported that Pt doping into IrOx‐based nanoframe is beneficial in both ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
65
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 47 publications
3
65
0
Order By: Relevance
“…25 A number of prior studies have evaluated developing improved acidic OER catalysts through interacting iridium and cobalt within iridium-cobalt nanowires, 3 iridium-cobalt porous nanocrystals, 26 iridium-cobalt oxide, 27,28 IrO 2 -Co 3 O 4 nanorods, 29 and cobalt-doped SrIrO 3 . 30 Nanoframe structures that combine iridium with Pt 31 or Ni and Cu 32 have been previously studied to enhance the activity and stability of oxygen evolution electrocatalysts. The catalyst structure and resulting OER activity and stability are highly dependent on the starting materials and chemical and electrochemical processes used to generate the active catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…25 A number of prior studies have evaluated developing improved acidic OER catalysts through interacting iridium and cobalt within iridium-cobalt nanowires, 3 iridium-cobalt porous nanocrystals, 26 iridium-cobalt oxide, 27,28 IrO 2 -Co 3 O 4 nanorods, 29 and cobalt-doped SrIrO 3 . 30 Nanoframe structures that combine iridium with Pt 31 or Ni and Cu 32 have been previously studied to enhance the activity and stability of oxygen evolution electrocatalysts. The catalyst structure and resulting OER activity and stability are highly dependent on the starting materials and chemical and electrochemical processes used to generate the active catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Choi et al reported control over the oxidation state of IrO x -based nanoframe structures by incorporating Pt dopants to prepare highly active and stable OER catalysts. [102] The degree of Pt doping in the IrO xbased nanoframes was controlled by controlling the geometric features of the nanoframes, specifically forming PtNi axis@ IrNi edge (PN-IN), PtNi axis@IrPtNi edge (PN-IPN), and IrPtNi edge without inner PtNi axis (IPN), followed by electrochemical activation in a 0.1 m HClO 4 electrolyte (Figure 15a,b). XPS analysis revealed that the relative Ir 4+ to Ir 3+ ratio differed according to the degree of Pt doping in the IrO x nanoframes; the activated PN-IN (a-PN-IN) with marginal Pt doping at the Ir edges possessed a much higher Ir 4+ to Ir 3+ ratio than the a-PN-IPN and a-IPN catalysts (Figure 15c,d).…”
Section: Charge Redistribution In the Catalystmentioning
confidence: 99%
“…Reproduced with permission. [102] Copyright 2020, Wiley-VCH. e-h) Ru-doped Pt 3 Cu catalysts (Ru 1 -Pt 3 Cu).…”
Section: Charge Redistribution In the Catalystmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 Furthermore, it is known that introducing Pt atoms into the structure of other active materials leads to the improved stability limits of such electrocatalysts. [27][28][29] The OER activity can be improved through increase of the electrochemically active surface area via shaping, using various supports 30 and/or synthesis of nanoparticles 20 or porous Pt. 31,32 However, the use of intermetallic compounds, combining Pt with other metals, to increase its inherent OER activity is represented scarcely in the literature.…”
Section: Introductionmentioning
confidence: 99%